Analogical hermeneutics and the humanities (Cultura Económica, 2022)
The aim of this article is to show the applicability of an Analogic Hermeneutics in the field of Humanities. In fact, they operate interpreting texts, and that is what hermeneutics teaches to do. However, nowadays we find univocal hermenetics and aequivocal hermeneutics, struggling among them, and we need an analogical hermeneutics which can be an intermediate. This way we shall avoid the univocism of positivisms and the aequivocism of posmodernisms. This struggle has conducted to an impasse, and we need already another way to more fertile lands.
Keywords: HUMANITIES; HERMENEUTICS; ANALOGY; POSITIVISM; POSMODERNISM